Rooting of yerba mate cuttings with different lengths - DUARTE, Manoela Mendes; MIRESKI, Maria Cecília; OLISZESKI, Afonso; WENDLING, Ivar; STUEPP, Carlos André (Revista Teste SPGG, 2019)
Due to its economic, social, and ecological potential, Ilex paraguariensis A. St. Hil is considered one of the most important native forestry species in southern Brazil, needing high production of quality plants to supply consumption. Therefore, vegetative propagation is a key technique since it enables plants production with higher standard and genetic quality. Several studies have focused on defining appropriate methods for rooting yerba mate cuttings, even though the overall rooting indexes are not yet considered appropriate. Thus, the objective of this study was to evaluate the rooting, root and aerial vigor of yerba mate cuttings and determine the best cuttings length for formation of clonal plants. Twenty parent trees were pruned and after five months epimoric sprouts were collected to prepare stem cuttings with lengths of 2 ± 0.2 cm, 4 ± 0.2 cm, 6 ± 0.2 cm, 8 ± 0.2 cm, 10 ± 0.2 cm and 12 ± 0.2 cm and diameter of 0.5 ± 0.2 cm. We planted cuttings in plastic boxes filled with substrate based on carbonized yerba mate matchsticks and vermiculite. After 120 days we evaluated the percentage of rooting, number of roots per cutting, average length of the 3 largest roots per cutting, cuttings with callus, cuttings with roots and callus, mortality, sprouts emission, and leaf maintenance. Our results show that rooting and vigor of roots in yerba mate stem cuttings are influenced by cuttings length, being 10 cm cuttings the most efficient for clonal propagation of the species.